If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3z + -3) = 60 Reorder the terms: 5(-3 + 3z) = 60 (-3 * 5 + 3z * 5) = 60 (-15 + 15z) = 60 Solving -15 + 15z = 60 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 15z = 60 + 15 Combine like terms: -15 + 15 = 0 0 + 15z = 60 + 15 15z = 60 + 15 Combine like terms: 60 + 15 = 75 15z = 75 Divide each side by '15'. z = 5 Simplifying z = 5
| -16t^2+65.5t+5.5=0 | | 12x-8+3x=4(x-2) | | x(x+1)(x+2)=15(x+1) | | 7-6x=-5-8x | | x+16+10=7x-10 | | .04y=656+x | | vx-11=4 | | L+12.2=23.9 | | ((12)(12))+((10)(10))=((c)(c)) | | 5(2x-3)-4(x-4)=-23 | | -187=17n | | x=656-.4y | | 2(7-7x)+2(x-7)=36 | | 7a+3b-8(9a-4b)= | | -3(x-3)=-33 | | y=2.5*12.5 | | 7-17=2x | | 24a-8-10a= | | 192=62+10x | | 9x^2+56x+80=0 | | 9t+4(2-t)=7t+16 | | 5x-5.26=-3.61 | | [2z-3]=-4z-1 | | 26=4b+42 | | -3x+10=5x-6 | | 8(7-y)-8=-16(y-2) | | 13+3x-4=6x-3 | | 21v^2-v-16=-6 | | 5n-9=36 | | 5n^2-11=-2n | | A-6=8 | | -x+3(x-4)=-2(3+x) |